Fluoropolymer‐Stabilized Chromophore–Catalyst Assemblies in Aqueous Buffer Solutions for Water‐Oxidation Catalysis. Issue 11 (23rd May 2017) - Eberhart, Michael S.; Wee, Kyung‐Ryang; Marquard, Seth; Skinner, Kasey; Wang, Degao; Nayak, Animesh; Meyer, Thomas J.
Abstract: Here, the application of the fluorinated polymer [Dupont AF, a copolymer of 4, 5‐difluoro‐2, 2‐bis(trifluoromethyl)‐1, 3‐dioxole and tetrafluoroethylene] is described in stabilizing phosphonate‐derivatized molecular assemblies on oxide electrodes. In the procedure, the polymer was dip‐coated onto the surfaces of oxide electrodes with pre‐bound, phosphonate‐derivatized chromophores and assemblies, including assemblies for water oxidation. The results of the experiments showed a high degree of stabilization by the added polymer and a demonstration of its use in stabilizing surface‐bound assemblies for water‐oxidation catalysis. Abstract : Layer up : A chemically stable fluorinated polymer overlayer stabilizes phosphonic acid‐bound chromophores and catalysts on metal‐oxide surfaces. The polymer overlayer prolongs the usable lifetime of electrodes with catalysts for water oxidation. Typically, phosphonic acid binding to metal oxides is unstable at pH>5. The polymer overlayers stabilize this binding at higher pH values at which water‐oxidation thermodynamics are more favorable.